Correction: A photoactive lysosome targeting RuII complex downregulates stemness genes in oral squamous cell carcinoma. Issue 2 (19th December 2022) - Roy, Souryadip; Mitra, Paromita; Acharya, Sourav; Roy, Shantanu Saha; Ghosh, Shilpendu; Maji, Moumita; Modak, Niladri; Ghosh, Nirmalya; Acharya, Moulinath; Singh, Sandeep; Mukherjee, Arindam
Abstract : Correction for 'A photoactive lysosome targeting Ru II complex downregulates stemness genes in oral squamous cell carcinoma' by Souryadip Roy et al., Inorg. Chem. Front., 2022, 9, 5840–5852, ; https://doi.org/10.1039/D2QI01079H .